Impact of Financial Structure on The Financial Stability: An Empirical Study in A Sample of Iraqi Companies - Hameed Yasir, Mohanad; Hussein Harjan, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The current study aims to reveal the impact of the sources of the financial structure that consists of (the right of ownership in book value to total assets and total short-term debt to total assets and the market value of shares to total assets and retained earnings to total assets) as independent variables, in financial stability as a dependent variable. In order to achieve the aims of the study and answer its questions, the study tested a sample of the industrial companies contributing, using that data published on the website of the Iraq Stock Exchange for the period (2010-2018). The sample includes (11) industrial companies listed on the Iraq Stock Exchange. The most important finding of the results is that financing the right of ownership in the book value to the total assets has a role in achieving financial stability for the industrial sample companies. In other words, the high percentage of financing the right to ownership in the book value to the total assets can increase the financial stability of companies through its impact on the cost of financing in general. The research concludes that it is necessary to keep the ownership rights high because that enables companies to obtain the necessary financing at the lowest costs, and reduce dependence on debt financing, which leads to financial stability.